Ekspresi Reseptor FcÎ³II (CD32)Monosit pada Pasien Infeksi Dengue dan Subyek Sehat - , Harina Salim ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Dengue infection is a global threat and an endemic or epidemic disease in almost countries especially in tropical and subtropical regions, including Indonesia. Since it was first discovered in 1968 until 2009, the World Health Organization (WHO) noted Indonesia as a country with the highest cases of dengue hemorrhagic fever (DHF) in Southeast Asia. Manifestations of dengue infection vary widely, and it can be asymptomatic or symptomatic, such as the undifferentiated fever, dengue fever (DF), DHF or dengue shock syndrome (DSS). Antibody-dependent enhancement (ADE) is one of the central hypotheses for the pathogenesis of DHF/DSS that hadbeen proposed 3 decades ago. Preexisting antibodies to one serotype form infectious immune complexes withheterotypic serotypes and bind to FcÎ³II receptor such as monocytes/macrophages. This facilitates the entry of dengue virus / DENV, replication, and spread which willincreasing the degree of the disease severity. This study is an observational analytic study with a cross-sectional design to determine expression of FcÎ³IIR (CD32) monocytes in patient with dengue infection and healthy subject. The study subjects were patients with DENV infection based on WHO 2011 criteria, hospitalized in RSUPDR. Sardjito Yogyakarta andRSUD Panembahan Senopati Bantul, and resident/relatives with consecutive selected and meet the criteria for inclusion or exclusion. Examination expression of FcÎ³IIR (CD32) monocytes in whole boodwith lyse no wash principle using flowcytometry. The results shown in the descriptive analysis and analysis of differences expression of FcÎ³IIR (CD32) monocytes in patients with dengue infection and healthy subjects.Expressionof FcÎ³IIR (CD32) monocytes in patients with dengue infection higher than healthy subjects.